2012
DOI: 10.4103/0972-2327.93282
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium-intracellulare brain abscess in HIV-positive patient

Abstract: Mycobacterial opportunistic infections are a major cause of morbidity and mortality among patients living with HIV (PLHIV) worldwide. Nontuberculous mycobacterial (NTM) infection is one of the leading causes of opportunistic infection in patients with advanced acquired immunodeficiency syndrome i.e., with CD4 count less than 50/cu.mm. Mycobacterium avium complex (MAC) is among the most common opportunistic bacterial infections in those patients with advanced immunodeficiency apart from cryptococcal meningitis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Furthermore, even in most cases, it is reported to occur in immunocompromised patients such as those with HIV infection, malignancy, etc. [ 3 8 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even in most cases, it is reported to occur in immunocompromised patients such as those with HIV infection, malignancy, etc. [ 3 8 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of NTM-CNS infection can vary and include headache, fever, seizures, altered consciousness, etc. [ 7 8 10 ]. They are nonspecific and difficult to distinguish from other CNS infections, making diagnosis challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 cases were due to MAC (13 %) [ 3 ]. Furthermore, an extensive search in the English literature found only 8 additional cases with MAC brain abscess (Table 1 ): 7/8 patients were HIV-positive or presented with an underlying immunodeficiency [ 4 , 9 , 12 17 ]. Males were infected 75 % of the time and the median age was 38 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that disseminated disease, previous neurosurgery, and trauma are leading factors for CNS infection [ 2 ]. The majority of cases involving MAC infection of the CNS are seen as opportunistic infections in patients with acquired immunodeficiency syndrome (AIDS) with a severely depressed CD4 count (<50 cells/μl) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Murray et al [7] described a case of CNS MAC in a patient following immune reconstitution with a CD4 count of 215/μL who had recently changed from multidrug anti-MAC medication to secondary prophylaxis with azithromycin. In 2011, Karne et al [8] reported an HIV infected patient (CD4 14) with a single MAC brain abscess causing mass effect and focal neurologic deficits including left hemiplegia requiring emergent drainage of the 5 cm × 4 cm × 4.5 cm abscess and clarithromycin and ethambutol treatment along with ART.…”
Section: Discussionmentioning
confidence: 99%